Teacher Talk In English Teaching And Learning Process At SMP N 1 Banyudono In 2015/2016 Academic Year - Nurma Setianingrum, Yunita, Prof. Dr. Endang Fauziati, M.Hum (2016)
This research has major objectives proposed by the researcher, they are (1) to identify the languages of Teacher Talk found in English teaching and learning process, (2) to identify the dominant language of Teacher Talk in English teaching and learning process, (3)to identify the types of Teacher Talk found in English teaching and learning process, and (4) to identify the dominant type of Teacher Talk in English teaching and learning process. Teacher Talk is a tool to make student understand with the lesson. The type of this research is descriptive qualitative research especially naturalistic study in analyzing the data. The data source of this study is taken from SMP N 1 Banyudono. Regarding with the method of collecting data, the researcher applies observation, interview as well as document analysis. The researcher uses FLINT theory as the way to find language used in Teacher Talk and type of teacher Talk based on language used. The result of this study indicates that first, there are five languages found in Teacher Talk, such as Javanese, Indonesian, English, Arabic, and Mixed languages. Second, the dominant language used of teacher talk in English teaching and Learning is mixed languages. Third, there are 11 types of Teacher Talk based on language used. 10 types from FLINT theory, and the new type found is greeting as another finding from the researcher. The most frequent type of teacher talk formed by three teachers was"ask question" (type 4). The percentage was 33.30% from 337 data for six meetings. Fourth, the dominant type of Teacher Talk based on language used is "ask question". The teacher tended to ask many questions to the student in order to make the class more active and to know whether the students understood or not. It was a way to make students understood with the lesson.